PENGEMBANGAN STRATEGI PEMASARAN UMKM AL-BAROKAH IBU ROSSI - Nur Asna Mahanani; Cucu Hayati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
The purpose of this study is to identify and develop marketing strategies that suit the needs of MSMES AL-BAROKAH IBU ROSSI. The research methods applied are case studies and surveys through interviews with the owner of MSME AL-BAROKAH, Mrs. Rossi, as well as secondary data analysis related to the industry and the latest market trends. The results showed that MSME AL-BAROKAH IBU ROSSI needs to adopt a marketing approach that focuses on target market and product differentiation. Recommended marketing strategies include clear target market identification, strong brand development, use of social media and digital marketing, and providing added value through superior customer service. In addition, collaboration with other parties, such as financial institutions, business partners, or local communities, can also increase MSME market visibility and access